Automatic wireless health instructor for schools and colleges - Jeyalakshmi Chelliah; Manjunathan Alagarsamy; Karthikram Anbalagan; Dineshkumar Thangaraju; Edwin Santhkumar Wesley; Kannadhasan Suriyan (Bulletin of Electrical Engineering and Informatics, 2022)
The suggested work demonstrates the preventive measures that can be used in schools and colleges during the present pandemic, which are the most important considerations once all of the institutions have reopened. Right now, sanitizers are the most important goods. According to WHO's new standards and regulations, a high level of sanitization is required to live. Despite the fact that all guidelines have been implemented, the majority of students are irresponsible, exacerbating the current scenario. To keep a student's hand sterilised, the proposed design incorporates an automatic hand sanitizer and a temperature detection system based on their ID card. The specific status of the student will be delivered to the class coordinator's mobile phone via genitourinary syndrome of menopause GSM whenever a person wishes to do it, even if there is no contact with the sanitising machine. Our method also uses a camera to snap a picture of the student, which can be viewed on a computer if any of the students do not answer. This also verifies the student's attendance, and the temperature of a specific student will be checked without the student's contact or touch in order to ensure safety and security. This allows everyone to keep an eye on the students while adhering to regulatory regulations.